Exploring the knowledge, attitudes, and perceptions of young men towards fertility in the UK: A cross-sectional survey - Jack Tighe; Emeka Okorocha; Anita Mitra; Nicholas Anson; Benjamin P. Jones; Rachel Roberts; Muna Elshieikh; Efstathios Theodorou; Jara Ben Nagi; Lorraine S. Kasaven (PLoS ONE, 2026)
Introduction Across many countries, paternal age at childbirth is rising, increasing exposure to age-related fertility decline. This study evaluated fertility-related knowledge, attitudes, and perceptions among young men. Methods An anonymous cross-sectional survey was distributed via social media between 13/02/2025 and 29/09/2025. UK adult males completed 54 close-ended questions covering participant characteristics, fertility knowledge, reproductive aspirations, and personal/socioeconomic influences. Results A total of 408 men participated in the survey, of whom 214 (52.5%) completed all components, with a median age of 34 years (interquartile range 31–38). Most were married (61.5%; N = 176), had degree-level education or higher (78.4%; N = 226), and were in full-time employment (85.4%; N = 246). Over half had no children (55.6%; N = 160). Most wished to have their first child between 30–35 years (64.5%; N = 71), and last between 36–40 years (64.3%; N = 119). More than half of the participants recognised that paternal age affects fertility (58.6%; N = 133). However, few were aware of the contribution of male-factor infertility (16.9%; N = 38), or the age at which semen quality declines (17.7%; N = 40). The majority understood that modifiable lifestyle factors influence semen quality (88.9%; N = 200), and either agreed or strongly agreed that smoking (99.1%; N = 211), recreational drug use (95.3%; N = 203), and radiation/chemical exposure (98.1%; N = 209) impacted male fertility. Many men (43.2%; N = 92) had never sought fertility information; among those who did, online medical websites were most common (32.9%; N = 70), while social media was rarely used (1.4%; N = 3). Key considerations influencing reproductive plans included biological parenthood (76.5%; N = 160), partner suitability (94.7%; N = 196), financial security (95.2%; N = 197), and suitable housing (72.4%; N = 150). Conclusion Young men demonstrated limited awareness of age-related fertility decline despite recognising lifestyle effects. Routine healthcare offers an opportunity for counselling to improve awareness, alongside consideration of socioeconomic factors. Findings are limited by a small, highly educated sample and possible self-selection bias. Trial registration number Imperial College Research Ethics Committee number: 700608.